Polynomials' question.
Q no 78
Attachments:
![](https://hi-static.z-dn.net/files/de4/b70e4fc59d6b3452d1bf67f335106cfc.jpg)
Answers
Answered by
3
mn(x^2+1)=x(m^2+n^2)
mnx^2 -x(m^2+n^2)+mn=0
mnx^2-xm^2-xn^2+mn=0.......... so by splitting the middle term
mx(nx-m)-n(nx-m)=0
therefore ( mx-n)(nx-m)=0
=> mx-n=0,. nx-m=0
=> x = n/m and x = m/n.
I hope this will help you
mnx^2 -x(m^2+n^2)+mn=0
mnx^2-xm^2-xn^2+mn=0.......... so by splitting the middle term
mx(nx-m)-n(nx-m)=0
therefore ( mx-n)(nx-m)=0
=> mx-n=0,. nx-m=0
=> x = n/m and x = m/n.
I hope this will help you
IITGenius:
i have a doubt
Similar questions
Math,
8 months ago
English,
8 months ago
English,
8 months ago
English,
1 year ago
World Languages,
1 year ago